Association between anxiety, depression and quality of life: study protocol for a systematic review of evidence from longitudinal studies. Issue 3 (4th March 2019) - Hohls, Johanna Katharina; König, Hans-Helmut; Quirke, Eleanor; Hajek, André
Abstract : Introduction: Evidence from individual longitudinal studies suggests that anxiety and depression may impact quality of life. However, systematic reviews synthesising current evidence have mainly focused on specific samples. Thus, the aim of this study is to synthesise evidence from longitudinal studies on the association between anxiety, depression and quality of life in a systematic review. Methods and analysis: A systematic review of evidence from longitudinal studies analysing the association between anxiety, depression and quality of life will be conducted, taking into account the current Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Several electronic databases from relevant fields of research (PubMed, PsycINFO, PSYNDEX, EconLit, NHS EED) will be searched in September 2018 using defined search terms, with an updated search planned. Moreover, reference lists of included studies will be searched manually. Study eligibility will be appraised in a two-step process against pre-defined inclusion/exclusion criteria. Primarily, information on study design and assessment, statistical methods, participant characteristics as well as results regarding our research question will be extracted. The quality of included studies will be assessed using an appropriate tool. Study selection, data extraction and assessment of study quality will be performed by two reviewers. Disagreements will be resolved through discussion or by inclusion of a third party. Results will be synthesised narratively in text and tables. Depending on the number and heterogeneity of the studies included, a meta-analysis will be performed. Ethics and dissemination: As no primary data will be collected, approval from an ethics committee is not required. Results will be disseminated through conference presentations and publication in a peer-reviewed, scientific journal. PROSPERO registration number: CRD42018108008.